Are People Altruistic When Making Socially Responsible Investments? Evidence From a tDCS Study - Yang, Xiaolan; Meng, Wenting; Chen, Shu; Gao, Mei; Zhang, Jian (Frontiers in Neuroscience, 2021)
Socially responsible investment (SRI) is an emerging philosophy that integrates social and environmental impacts into investment considerations, and it has gradually developed into an important form of investment. Previous studies have shown that both financial and nonfinancial motivations account for SRI behaviors, but it is unclear whether the nonfinancial motive to adopt SRI derives from investors' altruism. This study uses neuroscientific techniques to explore the role of altruism in SRI decision-making. Given that existing evidence has supported the involvement of the right temporoparietal junction (rTPJ) in altruism and altruistic behaviors, we used transcranial direct current stimulation (tDCS) to temporarily modulate activity in the rTPJ and tested its effect on charitable donations and SRI behaviors. We found that anodal stimulation increased the subjects' donations, while cathodal stimulation decreased them, suggesting that tDCS changed the subjects’ levels of altruism. More importantly, anodal stimulation enhanced the subjects' willingness to make SRIs, while cathodal stimulation did not have a significant impact. These findings indicate that altruism plays an important role in SRI decision-making. Furthermore, cathodal stimulation changed the subjects’ perceived effectiveness of charitable donation but not that of socially responsible fund. This result may help explain the inconsistent effects of cathodal stimulation on charitable donations and SRI behaviors. The main contribution of our study lies in its pioneering application of tDCS to conduct research on SRI behaviors and provision of neuroscientific evidence regarding the role of altruism in SRI decision-making.